The Corelation of Pandemic and Indonesia Presidency of G20 in The Capital Market G20 Member Countries - Rahma Tri Benita (Pusbindiklatren Bappenas, 2022)
The correlation between the capital market of G20 member countries is important to analyze.Depending on a country’s economy, capital market integration may have different effects. A more intensebilateral relationship (trade intensity) can significantly affect the movement of capital market sharesbetween countries. The current research used the Multivariate GARCH Model/DCC-GARCH method. Thecondition of capital market integration before the Indonesian G20 Presidency showed that Indonesia(JKSE) had the strongest integration with Australia (ASX) (0.563814) and South Korea (KOSPI) (0.542470).After the G20 presidency, Indonesia (JKSE) had the strongest capital market integration with India (NSE)(0.507229) and the USA (NYSE). It was also found that China (SSE) had an integration with South Korea(KOSPI), while Germany (DAX) and Australia (ASX) had an integration with the UK (FTSE100). Theconclusion is that the higher autocorrelation, the higher the effect of the volatility of stock marketmovements in the two countries involved. Furthermore, capital market integration can be influenced bygeospatial and economic relations.